Superresolution imaging of transcription units on newt lampbrush chromosomes - Kaufmann, Rainer; Cremer, Christoph; Gall, Joseph G. (Chromosome research, 2012)
We have examined transcription loops on lampbrush chromosomes of the newt Notophthalmus by superresolution microscopy. Because of the favorable, essentially two-dimensional morphology of these loops, an average optical resolution in the x-y plane of about 50 nm was achieved. We analyzed the distribution of the multifunctional RNA-binding protein CELF1 on specific loops. CELF1 distribution is consistent with a model in which individual transcripts are tightly folded and hence closely packed against the loop axis.